Nano‐electromanipulation of Spin Crossover Nanorods: Towards Switchable Nanoelectronic Devices. (27th January 2013) - Rotaru, Aurelian; Dugay, Julien; Tan, Reasmey P.; Guralskiy, Ilya A.; Salmon, Lionel; Demont, Philippe; Carrey, Julian; Molnár, Gábor; Respaud, Marc; Bousseksou, Azzedine
<x xml:space="preserve">Abstract</x> The nanoscale manipulation and charge transport properties of the [Fe(Htrz)2(trz)](BF4) spin‐crossover compound is demonstrated. Such 1D spin‐crossover nanostructures are attractive building blocks for nanoelectronic switching and memory devices. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>